Requirements Analysis of Tuberculosis Screening Information System Using PIECES Framework - Dewi, Adinda Cipta; Adi, Kusworo; Martini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tuberculosis (TB) remains a global health threat, especially in low and middle income countries, including Indonesia. In Indonesia, there is a surge in TB cases due to the lack of detection and treatment of TB that does not reach the target. To achieve TB elimination by 2030 in accordance with the global target, Indonesia must reach the target of finding cases at least 90% of estimated cases. TB case finding through the screening activities is the first step of TB control to reduce morbidity and mortality. This study aims to analyze the requirements of the TB screening information system. The analysis was conducted based on the PIECES Framework as a method of analysis as a basis for obtaining more specific issues. The results of the analysis resulted in the need for an information system that can be accessed by the Health Office, Health Center, and the community with several requirements including providing a menu of counseling schedules and consultation messages, adding data on educational materials, producing an information dashboard, a system equipped with a database for storage and a password for security, and producing accurate and real time information for the requirements of prevention and intervention efforts